Definition of Procedural Aspects and Good Practices for the Advisory Service of the Online Learning Program at the Distance State University of Costa Rica - Mora-Vicarioli, Francisco (2017)
This article shows the results of a research study whose main objective was to evaluate the contributions of the consulting process facilitated by the Online Learning Program (PAL). This consulting process is offered to tutors, coordinators and chair managers or program coordinators in the virtualization processes of their subjects or online courses at the State Distance University (UNED) of Costa Rica, to get an organization and appropriate mediation of virtual learning environments accordingly. The above with the purpose of generating an approach to procedural aspects and good practices that are carried out from the counseling process. An online instrument was applied to a population of counseling users. From the analysis performed on the instrument, a series of findings was obtained in terms of perceived benefits, relevance of the design, and organization that favors counseling for the improvement of online courses, their organization design, mediation, as well as the value of the manuals provided by the PAL to perform configuration processes on the platforms, among other aspects.